Improve a college management system based mobile application - Mahmoud, Magdy Shayboub A (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
College Management System (CMS) is an application currently based on the most popular operating systems such as Android and IOS, and it is considered one of the very useful systems for students and employees of academic and administrative colleges. Maintaining reduced time and ease of use while ensuring confidentiality and security are among the most important features of this proposed improvement. This paper focuses on how to improve and raise the efficiency and effectiveness of this system's performance and that is by allowing students. Faculty members and parents to access it easily and secure, in order to follow up and know the academic level of their students by using their smartphones anywhere and anytime. So we implemented this improvement to raise the quality of the current educational process. Also, in the event of a decline in the academic level of students or an increase in the percentage of absenteeism in the courses registered for them, this application sends warning or alert messages to all students and their parents. Also, this application has been built and improved to be more secure and reliable, by not allowing students or their parents to modify or delete their data. Finally, this application has been optimized to be easy to use and to deal with all different smart device operating systems.